Machine for Wheat Sowing without burning of paddy straw - Narang, Mahesh Kumar; Chandel, Rupinder; Thakur, Surinder Singh (Indian Farming, 2017)
By using Happy Seeder, machine paddy straw can be managed in thefield without burning and by using as a mulch. To solve the problem ofsowing of wheat without burning is possible by using this machine.